UNDERLYING MASTER NARRATIVE AND COUNTER-STORIES ON SELECTED AMERICAN ONLINE NEWS - Irma Febriyanti (International Journal of Humanity Studies (IJHS), 2020)
This paper extrapolates the contrasting discourse of master narrative and counter stories through an analysis of online news articles dealing with the marginalization of African-American students in Newark. The discourse of master narrative works to maintain the ongoing racism that limits the opportunity of African-American community in Newark educational field. The claim of equal opportunity, as is propagated by the discourse of Cami Anderson, the superintendent of Newark works to conceal the prevailing ideology of Whiteness and color-blind view that deny special privileged to the Whites. Employing Faircloughs CDA (2010) under the framework of Critical Race Theory (CRT), the study underlines micro-structures of linguistic features within the wider scope of racism in American education. This paper argues that Whiteness as ideology remains prevalent in American educational system, and one avenue to subvert this view by increasing the involvement of marginalized group in the policy making decision. The discourse of the public, as seen in Barakas narration aligns with the African-American communitys struggle for equal access to through its advocatory tone as a catalyst for social change.